Some Properties of Platelet Cofactor I Concentrates of Bovine Origin - Baker, William J.; Seegers, Walter H. (Thrombosis and Haemostasis, 1960)
Platelet cofactor I preparations from bovine plasma were studied from the viewpoint of stability in the presence of chemicals selected strategically. The preparations were of high quality having about 86 per cent of the protein as one component by ultracentrifuge analysis. The activity was easily destroyed with hydrogen peroxide, sodium sulfite, phenylhydrazine, formalin, acetone, and by the process of freeze drying. The activity was not lost in the presence of oxygen, ascorbic acid, cysteine, merthiolate, parachloromercuribenzoate or 0.5 per cent phenol. In the native plasma the activity is not adsorbed on barium carbonate, barium sulfate, or magnesium hydroxide. Nor is it destroyed by ether; but, in purified form it is adsorbed on these adsorbants and is destroyed by ether. In the purified preparations the activity was not adsorbed on IRC-50 resin thus making it possible to use this adsorbant to remove any thrombin that might be added to a platelet cofactor I preparation. By this technic it was possible to show that thrombin alone does not easily destroy platelet cofactor I activity.